Architecture of a Species: Phylogenomics of Staphylococcus aureus. Issue 2 (February 2017) - Planet, Paul J.; Narechania, Apurva; Chen, Liang; Mathema, Barun; Boundy, Sam; Archer, Gordon; Kreiswirth, Barry
Abstract : A deluge of whole-genome sequencing has begun to give insights into the patterns and processes of microbial evolution, but genome sequences have accrued in a haphazard manner, with biased sampling of natural variation that is driven largely by medical and epidemiological priorities. For instance, there is a strong bias for sequencing epidemic lineages of methicillin-resistant Staphylococcus aureus (MRSA) over sensitive isolates (methicillin-sensitive S. aureus : MSSA). As more diverse genomes are sequenced the emerging picture is of a highly subdivided species with a handful of relatively clonal groups (complexes) that, at any given moment, dominate in particular geographical regions. The establishment of hegemony of particular clones appears to be a dynamic process of successive waves of replacement of the previously dominant clone. Here we review the phylogenomic structure of a diverse range of S. aureus, including both MRSA and MSSA. We consider the utility of the concept of the 'core' genome and the impact of recombination and horizontal transfer. We argue that whole-genome surveillance of S. aureus populations could lead to better forecasting of antibiotic resistance and virulence of emerging clones, and a better understanding of the elusive biological factors that determine repeated strain replacement. Trends: Staphylococcus aureus is characterized by both vertical and horizontal evolution. The vertical historical signal is often strong enough to make phylogenetic reconstruction meaningful and useful. The core genome of S. aureus can be defined in multiple ways, but ubiquitous genes are not always phylogenetically congruent. Conversely, genes that agree phylogenetically are not always ubiquitous. Genomic variation in S. aureus is discontinuous with distinct subdivisions called clonal complexes. The multifactorial forces shaping the structure of variation in S. aureus probably include bacterial competition and barriers to genetic exchange. Studies on the closest related species to S. aureus may help to infer traits of the common ancestor. Whole-genome surveillance will replace other forms of molecular typing, providing data for understanding the evolutionary dynamics.